The settler-colonial imagination: Comparing commemoration in Saskatchewan and in Québec. (August 2019) - Caldwell, Lynn; Leroux, Darryl
The authors present a comparative analysis of the Saskatchewan Centennial celebrations (2005) and the Québec quatercentenary celebrations (2008) informed by critical race theory, cultural studies, and studies of commemoration as overarching frameworks of analysis. This collaborative work considers two sites rarely analyzed together and examines how these major commemorative events narrate and represent relations among settlers and Indigenous peoples in Saskatchewan and in Québec. The analysis focuses on two significant events in each commemorative celebration: the Centennial Gala in Saskatchewan and Rencontres [Encounters] in Québec. While the contexts and narratives differ in significant ways, the two commemorations reveal their mutual investments in a national settler project. The authors contend that examining how Canada as a nation is remembered and currently imagined through such disparate sites and local histories provides critical insight into ongoing contentions about its constitution as a White settler society.